2016
DOI: 10.1159/000448339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and a Novel Prevention Technique for Inguinal Hernia after Robot-Assisted Radical Prostatectomy

Abstract: Introduction: To evaluate the incidence and risk factors for postoperative inguinal hernia (IH) after robot-assisted radical prostatectomy (RARP) and to assess whether a newly developed prevention technique reduces the incidence of IH after RARP. Methods: We included 161 consecutive patients (322 groins) who underwent RARP between September 2011 and October 2013. The prevention technique was as follows: (1) sufficient incision of peritoneum around the internal inguinal ring; (2) separation of spermatic vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…12 A PPV visualized at the time of MIRP was another significant risk factor for IH development. 7,14,19 An IH developed after RARP in 18% vs 6.4% of men with vs without a PPV. 7 Lee et al observed similar results in which a post-RARP IH developed in 26.5% of men with a PPV compared to 1.9% with no PPV.…”
Section: Predictive Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…12 A PPV visualized at the time of MIRP was another significant risk factor for IH development. 7,14,19 An IH developed after RARP in 18% vs 6.4% of men with vs without a PPV. 7 Lee et al observed similar results in which a post-RARP IH developed in 26.5% of men with a PPV compared to 1.9% with no PPV.…”
Section: Predictive Factorsmentioning
confidence: 97%
“…7,14,19 An IH developed after RARP in 18% vs 6.4% of men with vs without a PPV. 7 Lee et al observed similar results in which a post-RARP IH developed in 26.5% of men with a PPV compared to 1.9% with no PPV. 14 Further, the PPV reduced the inguinal hernia-free ratio time to IH development compared to that in men with no PPV (mean AE SD 12.9 AE 9.2 vs 15 AE 7.4 months).…”
Section: Predictive Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Shimbo et al . postulated that the peritoneum and vas deferens were stretched during urethrovesical anastomosis, resulting in a medial shifting of the internal ring, with subsequent widening leading to IH development . Moreover, Lee et al .…”
Section: Mechanism Of Ih Development After Rpmentioning
confidence: 99%
“…Shimbo et al postulated that the peritoneum and vas deferens were stretched during urethrovesical anastomosis, resulting in a medial shifting of the internal ring, with subsequent widening leading to IH development. 25 Moreover, Lee et al reported that a patent processus vaginalis, which is a peritoneal protrusion toward the deep inguinal ring, is an important risk factor for IH after RARP. 26 As discussed above, Kaiho et al proposed that repeated straining for urination pushes the small intestine into the funnel-shaped processus vaginalis, which can easily occur following release of the vas deferens from the prostate during RP.…”
Section: Mechanism Of Ih Development After Rpmentioning
confidence: 99%